2023
DOI: 10.3390/cancers15082394
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tumor and Immune Tumor Microenvironment of Primary Tumors and Metastatic Sites in Advanced Renal Cell Carcinoma Patients Based on Response to Nivolumab Immunotherapy: Preliminary Results from the Meet-URO 18 Study

Abstract: Background: Prognostic and predictive factors for patients with metastatic renal cell carcinoma (mRCC) treated with immunotherapy are highly warranted, and the immune tumor microenvironment (I-TME) is under investigation. Methods: The Meet-URO 18 was a multicentric retrospective study assessing the I-TME in mRCC patients treated with ≥2nd-line nivolumab, dichotomized into responders and non-responders according to progression-free survival (≥12 months and ≤3 months, respectively). The primary objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…The results derived from the IHC analysis of our sample are quite similar to those previously reported in literature, particularly for ratio between CD4+ and CD8+ cells [ 18 ]; only a third of patients presented PD-L1 CPS above 1. Tumors without clear cell component were associated with higher ratio between CD80+ and CD163+ immune cells, reflecting distinct macrophage population between ccRCCs and nccRCCs [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…The results derived from the IHC analysis of our sample are quite similar to those previously reported in literature, particularly for ratio between CD4+ and CD8+ cells [ 18 ]; only a third of patients presented PD-L1 CPS above 1. Tumors without clear cell component were associated with higher ratio between CD80+ and CD163+ immune cells, reflecting distinct macrophage population between ccRCCs and nccRCCs [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Rebuzzi et al demonstrated a strong correlation between the presence of specific immune cell types – particularly CD8 + T cells, CD4 + T cells, and PD-L1 expression – and patient responses to nivolumab treatment. 48 This correlation aligns with findings by Brown et al, who identified distinct expression patterns of immune markers differentiating responders from non-responders to ICIs. 49 These patterns are potentially predictive of treatment outcomes, suggesting that a nuanced understanding of tumor-infiltrating lymphocytes (TILs) could substantially refine the personalization of immunotherapy in RCC.…”
Section: Discussionsupporting
confidence: 89%